Using a carbon fiber sizing to tailor the interface-interphase of a carbon nanotube-polymer system. (December 2022) - Kirmani, Mohammad Hamza; Jony, Bodiuzzaman; Gupta, Kishor; Kondekar, Neha; Ramachandran, Jyotsna; Arias-Monje, Pedro J.; Kumar, Satish
Abstract: The primary goal of this work is to integrate a critical step (sizing application to fiber) of conventional carbon fiber-reinforced composite (CFRPs) manufacturing to carbon nanotube composite fabrication. A polyimide-based (Hydrosize HP 1632) sizing agent was used in studying the effect of sizing on interface-interphase properties of the CNT-BMI composite system. The effect of CNT and degree of functionalization and defects (DOFD) of CNTs in the cure kinetics and reaction of polyimide-based sizing was investigated via DSC and XPS analysis. The DSC results showed that the presence of CNTs changes the cure kinetics of the sizing agent, and functionalized CNTs have the most prominent effect compared to unfunctionalized CNTs as it changes the endothermic curing of pristine sizing to exothermic curing by addition of 25 wt% functionalized CNTs. Then the effect of sizing in CNT on the CNT/BMI composite interface-interphase was investigated by studying the cure kinetics of the high strength BMI matrix. Thermomechanical properties, molecular heterogeneity, and molecular hierarchy of the nanocomposite were studied and presented. The outcome of this study demonstrates the CNTs with sizing can significantly alter the cure reactions of the resin as well as the structure and thermo-mechanical properties of the CNT polymer nanocomposites. Graphical abstract: Image 1